Hubungan antara Biaya Transaksi dan Post-Earnings Announcement Drift: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEJ - MARFUAH MARFUAH (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to test the relationship between the transactions costs and post-earnings announcement drift. Share price and annual rupiah trading volume are chosen as proxies for the inverse of direct and indirect costs of transactions.On the basis of data of companies listed in the Jakarta Stock Exchange during the period of 1995 and 1996, the empirical test shows that there was a positive relationship between transactions costs and post-earnings announcement drift. This result indicates that transactions costs are an important determinant of the efficiency of capital markets. The results of this paper are consistent with an informational efficiency perspective that firms with high transactions costs can display significant mispricing or dritf, while those with low transactions costs are unlikely to be mispriced (Bhushan, 1994).